THE RELATIONSHIP BETWEEN SELF EFFICACY AND MATHEMATICAL CONNECTION SKILLS WITH STUDENTS"™ NUMERAC SKILLS - Mustofa, Mustofa; Mulyono, Mulyono; Mariani, Scholastika; Agoestanto, Arief (Jurnal Pendidikan Matematika dan IPA, 2025)
Numeracy ability is the ability to think logically and systematically in solving contextual problems based on data and numbers. However, students' numeracy ability in Indonesia, including in Central Java, is still relatively low. This study aims to determine the relationship between self-efficacy and mathematical connection ability simultaneously on students' numeracy ability on the material of arithmetic sequences and series in class X MANU 3 Ittihad Bahari Bonang Demak. This study uses a quantitative approach with a correlational method. The research sample was taken using a cluster random sampling technique, and two classes were obtained, namely class X.1 and X.2. The research instruments were in the form of a self-efficacy questionnaire and a descriptive test to measure mathematical connection and numeracy abilities. Data analysis was carried out using multiple linear regression tests using SPSS 25. The results of the study showed that there was a significant positive relationship simultaneously between self-efficacy and mathematical connection ability on students' numeracy abilities, with a coefficient of determination (R ²) value of 0.599. This means that the two independent variables contributed 59.9% to students' numeracy skills, while 40.1% was influenced by other factors. These results indicate the importance of the role of self-efficacy and mathematical connections in improving students' numeracy skills, as well as being the basis for further research to examine other factors that contribute to the development of numeracy skills.